PENGENALAN BAHAYA RADIASI DALAM KEHIDUPAN SEHARI-HARI DI SMA 2 SIAK - Yoshandi, T. Mohd.; Aprillia, Ghea (Awal Bros Journal of Community Development, 2024)
This research aims to introduce the dangers of radiation in everyday life to SMA 2 Siak students as an effort to increase awareness and understanding of the impacts of radiation exposure. Radiation, both ionizing and non-ionizing, can be found in various aspects of life, from nature to modern technological devices. Although most radiation is low risk, excessive exposure can harm health, including increasing the risk of cell disorders and cancer. Through literature study and outreach methods, this research succeeded in mapping radiation sources, explaining possible health impacts, and providing education regarding mitigation steps that students can take. The results show the need for continued education and the development of appropriate safety guidelines so that students can be wiser in interacting with radiation sources in their surrounding environment